A review of synthesis strategies for MOF-derived single atom catalysts - Hwang, Jongkook (Korean Journal of Chemical Engineering, 2021)
Single atom catalysts (SACs) have attracted great attention as promising catalysts that integrate the benefits of both heterogeneous and homogeneous catalysts. SACs exhibit unique properties that are otherwise difficult to achieve, such as high atom utilization efficiency, unprecedentedly high catalytic activity and selectivity. However, it still remains a great challenge to prepare stable SACs without particle aggregation and sintering. Among the various fabrication methods for SACs, metal-organic framework (MOF)-derived synthesis routes have shown great potential by taking advantage of MOFs’ high structural/chemical tunability, large surface area and high porosity. In this review, the synthesis strategies for MOF-derived SACs are comprehensively summarized and classified into five classes, metal node modification, ligand modification, guest encapsulation, migration and trapping, and others. The current challenges and future opportunities of MOF-derived SACs are further discussed. This review will be useful for the rational design of MOF-derived SACs for various catalytic reactions.
Keywords: Metal-organic Framework-derived Materials; Metal-organic Frameworks; Single Atom Catalyst